Mechanical properties of glass-reinforced composite/perforated metal sheet hybrids. (1st October 2020) - Alikhani, Arman; Nedoushan, Reza Jafari; Dastan, Tohid; Yu, Woong-Ryeol
Abstract: The mechanical properties of a hybrid structure consisting of a glass–epoxy composite and a perforated metal sheet were evaluated. The composite, hybrid, and resins were produced and their tensile behaviors were measured. Finite-element (FE) modeling was then used to predict the material's properties, based on the constituent properties, and also to analyze the stress distribution in each material. A new micromechanical model was developed to predict the hybrid's modulus and strength at different stages of deformation. Both the FE and micromechanical modeling accurately predicted these properties. It was also found that perforating the metal layer of a composite-metal hybrid can increase the specific strength of the material.